2015 IEEE International Conference on Consumer Electronics (ICCE) 2015
DOI: 10.1109/icce.2015.7066370
|View full text |Cite
|
Sign up to set email alerts
|

Using handheld devices to sup port augmented reality-based maintenance and assembly tasks

Abstract: This paper studies the opportunities coming from the use of consumer devices like smartphones and tablets to perform maintenance and assembly procedures with Augmented Reality (AR). Pros and cons are evaluated by comparing completion times and errors made while executing a maintenance procedure with an AR-based tool and paper-based instructions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 7 publications
1
34
0
1
Order By: Relevance
“…Havard [36] demonstrated how AR can help in disassembly operations utilizing the task of dismounting a pc blower. Sanna [23] aimed to gather data of non-expert maintainers using AR. For this reason, he considered a maintenance procedure of a notebook.…”
Section: Field Of Applicationmentioning
confidence: 99%
See 4 more Smart Citations
“…Havard [36] demonstrated how AR can help in disassembly operations utilizing the task of dismounting a pc blower. Sanna [23] aimed to gather data of non-expert maintainers using AR. For this reason, he considered a maintenance procedure of a notebook.…”
Section: Field Of Applicationmentioning
confidence: 99%
“…Authors sometimes refer to it as "collaborative maintenance" or "remote assistance". The application of AR for enhancing remote maintenance is mentioned in several papers [11], [19], [23], [28], [29], [36], [37], [39], [51]. Wang [37] reported that traditional remote assistance made "on-the-phone" cannot satisfy current technology complexity.…”
Section: Field Of Applicationmentioning
confidence: 99%
See 3 more Smart Citations